NRF2/miR-140 signaling confers radioprotection to human lung fibroblasts. Issue 1 (1st December 2015) - Duru, Nadire; Gernapudi, Ramkishore; Zhang, Yongshu; Yao, Yuan; Lo, Pang-Kuo; Wolfson, Benjamin; Zhou, Qun
Highlights Ionizing radiation induces BRCA1-dependent activation of NRF2 in human lung fibroblasts. BRCA1 activates NRF2 through the negative regulation of KEAP1. miR-140 is a novel target gene for NRF2 in human lung fibroblasts. BRCA1/NRF2/miR-140 signaling axis confers radioprotection to human lung fibroblasts.